Numerical Investigation of Dynamics Stall on Vertical Axis Wind Turbine (Advances in Applied Mathematics and Mechanics, 2025)
Dynamic stall poses a significant aerodynamic challenge for vertical axiswind turbines (VAWTs) and serves as a key impediment to enhancing their overallefficiency. Consequently, to elucidate the underlying mechanism of dynamic stall andfacilitate a clearer understanding of the entire dynamic stall process, a numerical investigation is conducted over the blades of a VAWT system. A two-dimensional numerical simulation is conducted by employing unsteady Reynolds-averaged Navier-Stokes(RANS) calculations with a Reynolds stress turbulence model. Four real-time key indicators are generalized to quantitatively characterize dynamic stall over the VAWTs.These indicators have been demonstrated to accurately predict the initiation and detachment times of the dynamic stall vortex (DSV), providing deeper insights into theunderlying mechanism of DSV development. Additionally, this study explores theimpact of blade thickness on the dynamic stall of VAWTs. Three airfoils from theNACA 4-digit series, each featuring distinct ratios of thickness to chord length, areexamined. As the blade cross-section transitions from NACA 0012 to NACA 0015 andNACA 0018, heightened blade thickness results in a delayed onset of dynamic stall,shifting from leading edge stall to trailing edge stall. Moreover, the blade thicknesssignificantly influences the efficiency of VAWT system, with increased airfoil thicknesscontributing to an improved utilization of wind energy.